A possible theory connecting seismicity and geomagnetic field - Moreno-Toirán, Bladimir (Minería y Geología, 2022)
A possible theory connecting geomagnetic field and earthquakes is presented. It was performed several hourly earthquakes distributions for different part of the world to explain, why bay-shape hourly distribution are clear for some areas, but not for others. In this sense, it was observed that earthquakes located in the intertropical zone reveal bay-shape earthquake distribution, but not defined shape is found for earthquakes outside the tropic. The answer is given based on geomagnetic flow orientation. The angle between the geomagnetic field direction and the Earth’s surface is almost parallel in the equator and orthogonal in the poles. Furthermore, considering the Laplace’s force law, the force experienced in the electrical conductor, in presence of magnetic field, is maximum when the angle between the magnetic flow direction and the electrical conductor is 90 degrees. Here, the electrical conductor is found on the global atmospheric electric circuit, where electrical current is flowing orthogonal to the Earth’s surface. The intertropical zone has angles between the geomagnetic flow vector and electric conductor more close to 90 degrees than middle latitudes and polar areas. The hourly earthquake distribution is modelled by the time-varying electrical potential in the global atmospheric electrical circuit, which is more significant in the intertropical zone. The effect of electricity on earthquakes is based on reverse piezoelectric phenomena.